2015
DOI: 10.1002/wea.2465
|View full text |Cite
|
Sign up to set email alerts
|

The UK’s wet and stormy winter of 2013/2014

Abstract: Editorialshould also be acknowledged: at the start of 2015 these still comprise over one-third of the UK's official climatological station network.The UK is a small and geographically complex country, and often a high density of weather stations is needed to capture localised features of our climate. As demonstrated during winter 2013/2014, even a small range of hills such as the North York Moors -rising to a modest 454m above sea level at the highest point -can have a profound effect on the weather. It is the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
89
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(96 citation statements)
references
References 18 publications
(24 reference statements)
5
89
1
Order By: Relevance
“…Thus, we find that parts of the proposed mechanism in previous studies (Huntingford et al 2014;Slingo et al 2014;Kendon and McCarthy 2015) linking the tropical west Pacific and European storminess show significant covariability, but we cannot find evidence for a direct relation from the beginning to the end of such a mechanism. In addition, the correlation between North American temperatures and windstorm anomalies drops to insignificant values when the winter 2013/14 is excluded from the analysis.…”
Section: S31contrasting
confidence: 82%
“…Thus, we find that parts of the proposed mechanism in previous studies (Huntingford et al 2014;Slingo et al 2014;Kendon and McCarthy 2015) linking the tropical west Pacific and European storminess show significant covariability, but we cannot find evidence for a direct relation from the beginning to the end of such a mechanism. In addition, the correlation between North American temperatures and windstorm anomalies drops to insignificant values when the winter 2013/14 is excluded from the analysis.…”
Section: S31contrasting
confidence: 82%
“…In short, the UK’s wet and storm winter was linked to record low temperatures on the North American continent 48 , and the contrast between the warm tropical Atlantic and cold air advecting south across the United States are likely to have been partly responsible for the persistence and unusual strength of the North Atlantic jet stream, which created the ideal conditions for generation of storms. Huntingford et al 16 argue that this in turn could have been related to the filling of the Aleutian Low in the northeast Pacific, which itself could be linked to high sea surface temperatures and a westward displacement of precipitation in the tropical Pacific.…”
Section: Discussionmentioning
confidence: 99%
“…A potential driver for positive sea surface temperature anomalies in the North Pacific and cold conditions in central North America further downstream is warm surface waters in the tropical west Pacific (Palmer 2014;Hartmann 2015). It has been suggested that increasing sea surface temperatures in the tropical west Pacific could also be the cause for extreme weather over the British Isles (Huntingford et al 2014;Slingo et al 2014;Kendon and McCarthy 2015). In line with this hypothesis, we first quantify the interannual variability of winter windstorm frequency over the North Atlantic/European region, which can be related to very low temperatures over North America.…”
mentioning
confidence: 99%